Effect of stress on the spontaneous combustion characteristic and molecular structure of coal - Fei Gao; Hai-xin Wang; Zhe Jia; Qi-hui Bai; Shu-Mao Zhao; Zheng Cui (Case Studies in Thermal Engineering)
To investigate the impact of stress on the low-temperature oxidation characteristic and molecular structure, temperature-programmed experiment and spectroscopy tests were conducted on Hegang lignite (HG) and Ciyaogou bituminous coal (CYG) under different stress. The results are the following: As stress increases, the CO concentration of the coal samples showed a decreasing-increasing-decreasing trend. The CPT of the two coal samples at 4 MPa, 20 MPa, and 30 MPa all were higher than 0 MPa. The highest temperatures reached were 160.5 °C for HG coal and 164 °C for CYG coal. In contrast, at 8 MPa and 12 MPa, the CPT of both coals were lower than 0 MPa. The lowest temperatures recorded were 144 °C for HG coal and 142 °C for CYG coal. This means that the tendency of coal spontaneous combustion showed a three-stage change with the increase of stress. In the 0–4 MPa, the content of aliphatic hydrocarbons, oxygen-containing functional groups, and structural parameter: d002, ID/IG, and AD/AG all decreased; In the 4–8 MPa, the above parameters all exhibited an increasing trend; In the 8–30 MPa, the above parameters all showed a downward trend again. The variation of coal microscopic structure under the stress effect was consistent with the effect of stress on the macroscopic oxidation characteristics of coal. The research results provided a theoretical basis for the difference in oxidation spontaneous combustion characteristics at different depths of coal seams.